Effects of postsilking weak‐light stress on the flour quality of spring maize. Issue 4 (6th June 2019) - Wen, Zhangrong; Shi, Kai; Lu, Weiping; Lu, Dalei
Abstract: Background and objectives: The low sunlight from June to July caused by cloudy weather in Southern China has a detrimental influence on the grain yield and quality of spring maize because this period overlaps with the grain filling stage. A field trial was conducted to study the effects of postsilking shading (30% and 50% light deprivation defined as moderate sunlight [MS] and severe shading [SS], respectively, and with plants under natural sunlight as the control) on grain weight, nutrient contents, pasting, and thermal properties in 2016–2017. Zhengdan958 (ZD958) and Suyu30 (SY30) were used as materials. Findings: MS and SS reduced the grain weight by 26.7% and 42.4% for ZD958 and by 17.4% and 25.7% for SY30 in 2016, respectively. In 2017, the decrease was 6.8% and 2.7% for ZD958 and SY30, respectively, and no difference was observed between MS and SS. Shading reduced the starch content and increased the protein content, and the effects were severe when a large amount of sunlight was deprived. SS increased the starch granule size in both varieties and years. MS resulted in an increase in 2016, but no increase was observed in 2017. Peak, trough, and breakdown viscosities decreased under shading. Similar reductions were generally observed between MS and SS. Shading exerted minimal effects on gelatinization and retrogradation temperatures, but the gelatinization enthalpy and peak height index gradually decreased with decreasing sunlight intensity. The retrogradation percentage increased under shading, and this increment was similar for MS and SS in 2016 and gradually intensified with increasing light deprivation in 2017. Conclusions: Shading reduced starch and amylose contents and increased protein contents and starch granule size. These effects induced low peak and breakdown viscosities and high retrogradation percentage. The high viscosities and low retrograde of SY30 indicated that it has better grain quality than ZD958. Significance and novelty: Shading deteriorates flour viscosity and increases the retrogradation tendency by reducing grain starch content and increasing protein content and starch granule size.